When solving equations using addition, they will have the form x − b = c. Recall that ax + b = c is a linear equation.
Thus, the equation x − b = c is a linear equation with a = 1 and a negative sign in front of b.
To see this, notice that 1.x = x and − = + -
Thus, we can rewrite x − b = c as
1.x + -b = c
You can solve x − b = c in one step.
When solving one step equation of the form x − b = c, rewrite x − b = c as
x + -b = c and add b to both sides of the equation.
We will illustrate with two examples.
Example #1
Solve x − 2 = 8
Example #2
Solve x − 4 = -6
You could also solve the equation x - 4 = -6 as shown below as well.
x - 4 = -6
x + -4 = -6
x + -4 + 4 = -6 + 4
x + 0 = -2
x = -2
Related content:
Easily solve equations of the form x − b = c with the click of a button!
Apr 20, 18 12:54 PM
Modeling exponential growth with the exponential function y = ab^x
New math lessons
Your email is safe with us. We will only use it to inform you about new math lessons.
Apr 20, 18 12:54 PM
Modeling exponential growth with the exponential function y = ab^x
Our Top Pages
Formula for percentage
Compatible numbers
Basic math test
Basic math formulas
Types of angles
Math problem solver
Algebra word problems
Surface area of a cube
Finding the average
Scale drawings
Everything you need to prepare for an important exam!
K-12 tests, GED math test, basic math tests, geometry tests, algebra tests.
Real Life Math Skills
Learn about investing money, budgeting your money, paying taxes, mortgage loans, and even the math involved in playing baseball.